O Evangelho de Homero: por uma outra história dos Estudos Clássicos - Rafael Guimarães Tavares da Silva (2022)
Homer is dead. Who killed Homer? The question posed by two American classicists, Victor Davis Hanson and John Heath (1998), echoes a traditional topos in the history of Classical Studies and constitutes the starting point for an investigation into the reality of a crisis in this discipline in contemporary times. This investigation analyzes the context of the last decades — especially the so-called culture wars — in order to understand the conflicts between different perspectives on Antiquity and its meanings for the present: between canon and cultural studies, between philology and theory, “classics” constitutes a battleground for classicists and intellectuals, both conservative and progressive. However, the questions raised by these debates suggest that some of the contemporary impasses have older roots, going back at least to the institutionalization of Altertumswissenschaft [the Science of Antiquity] in the German university of the 19th century, with its fusion of humanist and historicist principles. The person responsible for proposing a modern discipline for the study of Antiquity is Friedrich August Wolf, author of the work that formalizes the “Homeric question” in Modernity (with his Prolegomena ad Homerum, 1795). These two sides of his intellectual work are deeply intertwined and reveal the extent to which a reflection on Homer and his poems underpins the idea that philology is practiced since Antiquity. In this sense, Homer would be not just a metonymy of Classical Studies, but a condition of possibility for its development from the ancients to the (post-)moderns. To investigate this hypothesis, developed by Wolf and assumed by scholars who wrote Histories of Classical Scholarship (during the 19th and 20th centuries), the strategy is to go back to the ancients and study their potentially philological practices in the light of the specificities of their historical contexts. Doing so, an outline of another history of Classical Scholarship emerges — from Homer to Wolf and beyond —, sketched from the oblique perspective of someone who keeps reflecting on contemporary reality and, becoming aware of his own history, seek to critically confront its problems.